The impact of technology on impaired awareness of hypoglycaemia in type 1 diabetes - Simon A. Berry; Iona Goodman; Simon Heller; Ahmed Iqbal (Therapeutic Advances in Endocrinology and Metabolism)
Iatrogenic hypoglycaemia remains a major barrier to optimal glycaemic control required to prevent long-term complications in people with type 1 diabetes (pwT1D). Hypoglycaemia is the consequence of the interaction between absolute or relative insulin excess from treatment and compromised physiological defences against falling plasma glucose. With a longer duration of diabetes and repeated exposure to hypoglycaemia, pwT1D can develop impaired awareness of hypoglycaemia (IAH). IAH increases the risk of severe hypoglycaemia six-fold, causing significant morbidity, and, if left untreated, death. Over the last few decades, a stepwise change in diabetes management has been the introduction and widespread uptake of novel technologies, including continuous glucose monitoring (CGM) and automated insulin delivery (AID) systems. These technologies aim to improve glycaemic control whilst minimising hypoglycaemia. Alarms and safety functions, such as suspension of insulin delivery, can help to reduce the hypoglycaemia burden. This review examines the role of continuous glucose monitors and AID systems in managing IAH, exploring evidence for their impact on symptomatic awareness and identifying areas for future research. In conclusion, there is strong evidence that CGM and AID systems improve glycaemic control and reduce the hypoglycaemia burden. However, despite the use of these technologies, severe hypoglycaemic episodes are not entirely eliminated, and it remains unclear whether their implementation restores the physiological symptoms and counter-regulatory response to hypoglycaemia.